Improving the efficiency of molecular replacement by utilizing a new iterative transform phasing algorithm. Issue 5 (15th July 2016) - He, Hongxing; Fang, Hengrui; Miller, Mitchell D.; Phillips, George N.; Su, Wu-Pei
Abstract : An iterative transform algorithm is proposed to improve the conventional molecular‐replacement method for solving the phase problem in X‐ray crystallography. Several examples of successful trial calculations carried out with real diffraction data are presented. Abstract : An iterative transform method proposed previously for direct phasing of high‐solvent‐content protein crystals is employed for enhancing the molecular‐replacement (MR) algorithm in protein crystallography. Target structures that are resistant to conventional MR due to insufficient similarity between the template and target structures might be tractable with this modified phasing method. Trial calculations involving three different structures are described to test and illustrate the methodology. The relationship of the approach to PHENIX Phaser‐MR and MR‐Rosetta is discussed.